A unique presentation of a complex haemorrhagic adrenal pseudocyst. (28th October 2016) - Geleit, Ryan James; Bhardwaj, Rakesh; Fish, David; Sriprasad, Seshadri
Abstract : A man aged 33 years presented with a 3-day history of left-sided testicular discomfort. Clinical examination revealed a large left-sided varicocele. He was referred for a testicular ultrasound, which demonstrated a moderate left-sided varicocele and an associated large suprarenal mass. An urgent (CT) scan was arranged which confirmed this, with associated compression of adjacent structures, including the left kidney and left renal vessels. The patient was admitted 1 week following the CT scan with features of sepsis. An inpatient adrenal MRI scan suggested the presence of a large left-sided haemorrhagic adrenal cyst. This was removed surgically through a left subcostal incision. Histology confirmed there was no malignancy. The patient was discharged and a follow-up CT scan at 6 months showed complete resolution of the cyst with no further testicular discomfort. This is the first known case of an adrenal cyst presenting with a varicocele.